1946
DOI: 10.1085/jgp.29.5.335
|View full text |Cite
|
Sign up to set email alerts
|

Anoxia and Brightness Discrimination

Abstract: , I Nature of WorkIt is the commonest of observations both in actual flying and in pressure chamber experiments that fights become dim at high altitudes and then brighten on return to low altitudes. These events are due to the absence and presence of an adequate oxygen supply, as can be shown by their easy elimination when sufficient oxygen is available.The phenomenon itself has been demonstrated quantitatively as a rise in threshold of the dark-adapted eye during anoxia by NicFarland and Evans (1939), by McF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1974
1974
1990
1990

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 16 publications
2
9
0
Order By: Relevance
“…Smith et al found their losses at 371ux whereas we used 175 lux. Previous investigators [15,31,32] report a greater sensitivity of the hypoxic visual system to reductions in illumination than may normally be found at sea level. The study of Bowman and Cole [4] suggests that color discrimination suffers from tritan-like defects somewhere below 10-15 lux at normal oxygen tensions.…”
Section: Degree and Type Of Color Loss Found At 12000 Feetmentioning
confidence: 88%
See 2 more Smart Citations
“…Smith et al found their losses at 371ux whereas we used 175 lux. Previous investigators [15,31,32] report a greater sensitivity of the hypoxic visual system to reductions in illumination than may normally be found at sea level. The study of Bowman and Cole [4] suggests that color discrimination suffers from tritan-like defects somewhere below 10-15 lux at normal oxygen tensions.…”
Section: Degree and Type Of Color Loss Found At 12000 Feetmentioning
confidence: 88%
“…Other authors have also concluded that both the rod and cone systems are affected by hypoxia [15,42] or that cone vision may even have a greater loss than rod vision [11]. Since both the rod and cone pathways are affected by hypoxia there may be some merit in the suggestion that pilots supplement their oxygen supplies in the daytime whenever optimum visual performance is required.…”
Section: Locus Of Hypoxic Color Lossesmentioning
confidence: 99%
See 1 more Smart Citation
“…Part of this slowing was attributed to visual degradation, because response time increased disproportionately when stimulus brightness was lowered. Vision is particularly sensitive to hypoxia (McFarland, 1963), with brightness discrimination showing a definite effect at 8000 feet (Hecht, Hendley, Frank, and Haig, 1946). This raises the possibility that visual factors influence the threshold dose-response function for the effects of hypoxia on perceptualmotor performance.…”
Section: -February 1987mentioning
confidence: 99%
“…These findings are directly consistent with the severity of exposure, and from the present data are consistent with the contrast relationships of the stimulus surround of the viewing situation. Curiously enough, despite the general finding that brightness sensitivity and dark adaptation are particularly affected by anoxia (hypoxia) (Hecht, et al (1946);McFarland and Halperin (1940)), it would appear that responding throughout the visual field under hypoxia can be greater* for a dim stimulus with good contrast than for other brighter stimuli at higher ambient illumination levels if the latter are at poorer contrast with the surrotmd. Thus, assessment of the effects of hypoxia on visual response must take account not simply of the virtual stimulus luminance, but rather of the functional visibility of the stimulus-background contrast relationships, assuming the stimulus to be above threshold value in the visual periphery.…”
Section: Resultsmentioning
confidence: 97%